Development of Teaching Materials for Reading Comprehension Skills Using the Graphic Organizer Media - Kurniaman, Otang; Zufriady, Zufriady; Noviana, Eddy; Afendi, Nofrico (Proceedings of the UR International Conference on Educational Sciences, 2018)
The development of teaching materials for teachers facilitates the learning process as a learning medium to transfer knowledge to students. Graphic organizer is a visual communication tool to express ideas and concepts to convey meaning. The development of media-based reading teaching materials graphic organizer uses development research methods by passing the defining phase which is carried out by two-aspect analysis, namely analysis of the needs and analysis of students, and the development stage is analyzed by the readers technical concepts and exercises in the reading process. The next stage of teaching materials is validated by experts and practitioners about the feasibility of the content obtained an average of 87 with the category Very decent to use in learning to read comprehension in class IV elementary school.